THE EFFECT OF COMPETENCE AND SUPERVISION ON THE PERFORMANCE OF GOVERNMENT SUPERVISORS AT THE INSPECTORATE OF DKI JAKARTA PROVINCE - Abdullah; Watriningsih; Nina Sundari (Universitas prof. Dr. Moestopo (Beragama), 2022)
This study aims to analyze how much influence competence and supervision have on the performance of the inspectorate of the DKI Jakarta Province Inspectorate. The survey method used during this study in which questionnaires were distributed to the respondents. Hypothesis analysis used simple and multiple regression techniques and continued with correlation. Validity test with n = 76 (respondents) and r-table = 0.227 on trial error analysis. The results of the study indicate that there is a smaller influence between Competence and Supervision of Government Performance Supervision, both independent and concurrently. The coefficients of the determinants of competence and supervision of government performance are 0.869 and 0.702%, respectively. This means that the influence of Competence and Supervision on Government Supervision Performance is respectively 86.9% and 70.2% and is mostly influenced by these factors. The coefficient of Competency Determination and Supervision concurrently Supervision of Government Performance is 0.884. This means that the simultaneous influence of Competence and Supervision on Government Supervision Performance is 88.4% and 11.6% is influenced by other factors.